Vanity Fair : A Novel Without A Hero - Thackeray, William Makepeace; Edited by Carey, John; Directed by Nair, Mira (London Penguin Books, 2004)
No one is better equipped in the struggle for wealth and worldly success than the alluring and ruthless Becky Sharp, who defies her impoverished background to clamber up the social ladder. Her sentimental companion Amelia, however, longs for caddish soldier George. As the two heroines make their way through the tawdry glamour of English society in the early 1800s, battles-military and domestic-are fought, fortunes made and lost. The one steadfast and honorable figure in this corrupt world is Dobbin, devoted to Amelia, bringing pathos and depth to William Thackeray's gloriously satirical epic of love and social adventure.
Include Notes.
Keywords: Social classes -- England -- Female friendship -- British